Pembuatan Biobriket Dari Cangkang Kemiri Melalui Proses Karbonisasi Dengan Bahan Perekat Tepung Tapioka - M. Fauzan Zufarsyarif (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
Increasing energy needs require the search for alternative energy. One alternative energy is charcoal biobriquettes which can utilize biomass waste. This research studies the characteristics of biobriquettes from candlenut shells with tapioca flour adhesive. This research was structured using a Randomized Block Design (RAK) model, namely particle size (60, 80, 100, 120 and 150 mesh) and adhesive composition (5, 10, 15, 20 and 25%). Clean candlenut shells were dried using a 1050C oven for 2 hours and the water content was calculated. Next, it is carbonized at a temperature of 400Â°C. The process of making biobriquettes begins with crushing the charcoal and filtering the charcoal granules to obtain granule sizes of 60 mesh, 80 mesh, 100 mesh, 120 mesh and 150 mesh. Then the charcoal is mixed with tapioca flour as an adhesive. Then the biobriquette dough is formed, then molded and dried in the oven at 1050C for 1 hour. Next, the biobriquettes were characterized including 5 parameters, namely water content, density, ash content, combustion rate and heating value test. The best results obtained from this research were obtained on sample A2 with a particle size of 60 mesh and an adhesive composition of 10% where the water content value was 4.70%, the ash content was 5.6%, the density was 0.536 g/cmÂ³, the heating value was 5,238 cal/g and a combustion rate of 0.160 g/minute. The results obtained in this research for water content, ash content and density are in accordance with Japanese, British and American standards. Then the calorific value meets SNI standards.